2021
DOI: 10.1590/0104-1428.20210044
|View full text |Cite
|
Sign up to set email alerts
|

Effects of gamma radiation on nanocomposite films of polycaprolactone with modified MCM-48

Abstract: The aim of this investigation was to assess the effects of gamma radiation on nanocomposite films (NC films) formed by PCL (polycaprolactone) with MCM-48 nanoparticles (PCL/MCM-48) and PCL with MCM-48 NPs modified with (3-aminopropyl)triethoxysilane (APTES) (PCL/MCM-48-NH 2 ). The nanocomposite films were obtained using the solvent casting method. After preparing the films, they were irradiated at 25 kGy in the presence of air and analyzed by X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 45 publications
(75 reference statements)
4
4
0
Order By: Relevance
“…It also showed mass loss events between 200 °C and 600 °C, which are described as the elimination of organic content, which corroborates that the surface of MCM-48 was modified with PVA. These results are in agreement with our previous study: where the surface of MCM-48 was modified with APTES, it was observed that modified MCM-48 had a first event close to 100 °C attributed to the elimination of water; and a second event which was assigned to the surface modification with APTES [ 35 ]. Pure PVA had a first mass loss between 60 °C and 200 °C originating from the loss of adsorbed water [ 53 ].…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…It also showed mass loss events between 200 °C and 600 °C, which are described as the elimination of organic content, which corroborates that the surface of MCM-48 was modified with PVA. These results are in agreement with our previous study: where the surface of MCM-48 was modified with APTES, it was observed that modified MCM-48 had a first event close to 100 °C attributed to the elimination of water; and a second event which was assigned to the surface modification with APTES [ 35 ]. Pure PVA had a first mass loss between 60 °C and 200 °C originating from the loss of adsorbed water [ 53 ].…”
Section: Resultssupporting
confidence: 93%
“…Table 2 shows that the T 5 , T 10 , T 50 , and T max values for F2 and F5 were similar before and after exposure at 25 kGy. These results are similar to those shown in our previous study for T 5 , T 10 , and T 50 for PCL/MCM-48 films irradiated at 25 kGy [ 35 ]. TGA data demonstrated that the thermal decomposition characteristics of F2 practically did not differ from the thermal decomposition characteristics exhibited by F5.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations